Estructura de la comunidad y relaciones espaciales de traqueofitas y briofitas en el páramo de El Ángel, sector “Lagunas del Voladero”, Carchi, Ecuador. - Pasquel Dávila, Daniela Salomé (2020)
This study describes the community structure patterns of tracheophytes and bryophytes and their spatial relations in El Ángel páramo, “Lagunas del Voladero” area, Carchi, Ecuador. In this area, I established N=60 small plots (2 m × 2 m) to sample both tracheophytes and bryophytes. These two evolutionary lineages were sampled using a nested design in which bryophytes were only sampled in the center 1 m × 1 m. Plots (N) were established in the following habitats: forest (N=10), hilltop with Espeletia pycnophylla (N=16), slope with E. pycnophylla (N=14), wetland valley with E. pycnophylla (N=10) and wetland valley with almost no E. pycnophylla (N=10). For each species, dominance, measured as vegetation cover (cm2), was estimated using a metallic grid. I found 111 tracheophyte species and 94 bryophyte species. The most speciose tracheophyte family was Asteraceae (19 spp.), whereas the most speciose bryophyte family was Plagiochilaceae (10 spp.). The most dominant families (in terms of vegetation cover) were Asteraceae and Poaceae for tracheophytes, and Bartramiaceae and Dicranaceae for bryophytes. At the species level, the most dominant tracheophytes were Calamagrostis intermedia and Espeletia pycnophylla, whereas the most dominant bryophytes were Breutelia tomentosa and Riccardia amazonica. According to species-area rarefaction curves, tracheophytes had higher species density than bryophytes, and both evolutionary lineages showed higher species density in upland habitats than in wetlands. NMDS analyses for both tracheophytes and bryophytes showed a community structure different for each habitat, except hilltop and slope which had the same structure. At the plot level, I found that bryophyte species density correlated positively with tracheophyte species density. On the other hand, dominance of bryophytes vs. dominance of tracheophytes did not show any correlation. Further, at plot level, there was no correlation between bryophyte dominance and the dominance of common tracheophyte growth forms: tussocks, basal rosettes, prostrate shrubs, or Espeletia pycnophylla. In conclusion, this study reports the community structure patterns of tracheophytes and bryophytes and their spatial relations in El Ángel páramo. This páramo has been well studied for tracheophyte diversity, but it is relatively unexplored for bryophytes. The results of this study about tracheophytes-bryophytes coexistence in páramo are important to better understand their ecological processes in this ecosystem.